The Creative Game Tools and Mother's Motivation to Know Educational for Children Aged 1-3 Years - Arso Wibowo, Dodik; Nurhayati, Enur (Chakra Brahmanda Lentera Institute, 2023)
Background: A mother's motivation to know about educational and creative game tools has an important role in optimal child growth and development according to age level so that it can be fulfilled properly. Educational and creative game tools are game tools that can optimise children's development according to their age and level of development. Examples of educational and creative games for children aged 1-3 years are drums, balls with sleighs inside, household items that do not break easily (plastic cups, spoons, plastic bottles, buckets, etc.), large blocks, cardboard, picture books, coloured pencils, plasticine, simple puzzles. The research aims to determine mothers' motivation to learn about educational and creative games for children aged 1-3 years in Tanjungsari Village, Sukorejo District, Blitar City. Methods: Research design using descriptive, Population 500, sample 50 respondents, using purposive sampling technique, research instrument using questionnaires; this research was carried out on March 20, 2023 - April 15, 2023, with the mother's motivation variable to know educational and creative game tools for children aged 1-3 year. Data were analysed using percentages and interpreted quantitatively. Results: The results of research from 50 respondents showed that all respondents had strong motivation (100%) because the majority of mothers had received information about educational and creative game tools. Mothers' motivation to find out about educational and creative game tools for children aged 1-3 years is influenced by several factors, namely age, education, occupation, whether they have received information, and where the information was obtained Conclusion: It is hoped that respondents will be able to maintain and motivate other mothers to seek more information to broaden their knowledge so that they are more motivated to know about the benefits and uses of educational and creative play equipment for children aged 1-3 years.